A Comparison of Two Approaches to Developing In-service Teachers' Knowledge and Strategies for Teaching Nature of Science. Issue 1 (2nd January 2017) - Vhurumuku, Elaosi; Chikochi, Andrew
Abstract : This paper reports the results of a study that compared two approaches to developing in-service teachers' subject matter knowledge and strategies for teaching nature of science. A treatment post-test only quasi-experimental research design was used. One group of in-service teachers ( n = 15) was taught using what is called a capsular approach. In this approach in-service teachers were first taught elements of the history, the philosophy, the sociology of science and scientific literacy and then introduced to strategies for teaching nature of science. Another cohort of in-service teachers ( n = 11) was taught using what is called a heuristic approach. In this approach, in-service teachers were not taught about the history of science, the philosophy of science, the sociology of science and scientific literacy, but only about the basic tenets of nature of science and strategies for teaching nature of science. Quantitative and qualitative data from the post-treatment was gathered through a Likert questionaire, semi-structured interviews and analysis of lesson plans. Statistical, typographical and interpretive comparative analysis of this data reveals that the capsular approach was more effective compared with the heuristic approach. Recommendations are made for explicitly developing teachers' pedagogical content knowledge for nature of science.